Force-velocity relationship in cycling revisited: Benefit of two-dimensional pedal forces analysis - Dorel, S.; Couturier, A.; Lacour, J.-R.; Vanderwalle, H.; Hautier, C.; Hug, F. (Medicine & Science in Sports & Exercise, 2010)
Purpose: Maximal cycling exercise has been widely used to describe the power-velocity characteristics of lower-limb extensor muscles. This study investigated the contribution of each functional sector (i.e., extension, flexion, and transitions sectors) on the total force produced over a complete pedaling cycle. We also examined the ratio of effective force to the total pedal force, termed index of mechanical effectiveness (IE), in explaining differences in power between subjects.